Windwitch - Dennard, Susan (Dennard, Susan. Witchlands novel., 2017)
"After an explosions ruins his ship, Prince Merik tries to expose his sister's treachery while fighting for the weak on the streets of the royal capital. Meanwhile, Aeduan, a Bloodwitch, and Iseult, a Threadwitch, form an unlikely alliance and travel together looking for Safiya, who has been shipwrecked with the Empress of Marstok in a land of pirates and is living every moment balanced on a knife's edge, trying to keep the pirates from unleashing war upon the Witchlands."--Adapted from book jacket.